The industrial revolution in world history - Stearns, Peter N., author.
1 online resource
Keywords: Now in its fifth edition, this book explores the ways in which the industrial revolution reshaped world history,covering the international factors that helped launch the industrial revolution, its global spread and its impact from the end of the eighteenth century to the present day. The single most important development in human history over the past three centuries, the industrial revolution continues to shape the contemporary world. Revised and brought into the present, this fifth edition of Peter N. Stearns' The Industrial Revolution in World History extends his global analysis of the industrial revolution. Looking beyond the West, the book considers India, the Middle East and China and now includes more on key Latin American economies and Africa as well as the heightened tensions, since 2008, about the economic aspects of globalization and the decline of manufacturing in the West. This edition also features a new chapter on key historiographical debates, updated suggestions for further reading and boxed debate features that encourage the reader to consider diversity and different viewpoints in their own analysis, and pays increased attention to the environmental impacts. Illustrating the contemporary relevance of the industrial revolution's history, this is essential reading for students of world history and economics, as well as for those seeking to know more about the global implications of what is arguably the defining socioeconomic event of modern times.